Exploring Listening Strategy Instruction through Action Research - Siegel, Joseph. author. aut Link
XVI, 259 p. 13 illus.
Keywords: Listening in a second language is challenge for students and teachers alike. This book provides a personal account of an action research intervention involving listening strategy instruction that investigated the viability of this innovative pedagogy in the Japanese university context.